Advances in the study of IL-17 in neurological diseases and mental disorders - Lu, Yu; Zhang, Piaopiao; Xu, Fenfen; Zheng, Yuan; Zhao, Hongyang (Frontiers in Neurology, 2023)
, a cytokine characteristically secreted by T helper 17 (Th17) cells, has attracted increasing attention in recent years because of its importance in the pathogenesis of many autoimmune or chronic inflammatory diseases. Latest studies show that neurological diseases and mental disorders are closely related to immune function and varying degrees of immune dysregulation may disrupt normal expression of immune molecules at critical stages of neural development. Starting from relevant mechanisms affecting immune regulation, this article reviews the research progress of IL-17 in a selected group of neurological diseases and mental disorders (Autism spectrum disorder, Alzheimer's disease, epilepsy, and depression) from the perspective of neuroinflammation and the microbiota-gut-brain axis, summarizes the commonalities and provides a prospective outlook of target application in disease treatment.